Archaeological surface visibility: a GIS model for the lago Posadas basin, Santa Cruz province, Southern Patagonia - Figuerero Torres, María José (2013)
Discovery of archaeological materials is at the heart of archaeological reconnaissance and survey whether for research or the management of cultural resources. Ground visibility refers to the environmental conditions exposing archaeological materials yet there is a great diversity in the ways this is observed, measured and reported or correlated with other environmental variables. This has a bearing on how visibility is considered when evaluating the representativeness of the results or when making comparisons with other regions. But in Patagonia greater control and comparability has to be balanced with the need to survey large research areas. We present a GIS model based on landforms and vegetation that are sensitive to the main features of present day climate that were analyzed employing comparable scales of resolution. The surface visibility model represents the potentiality of detecting archaeological materials and thus can be used as a tool in planning coverage and selecting the best survey techniques as well as in interpreting survey results. This is relevant for Patagonia where large areas with both stratified occupations and artifact scatters must be surveyed and where the densities of artifact distributions are used in interpreting the intensity of land use.